The Role of Mothers and Children in the Art of Salawat Dulang by the Sinar Barapi Group - Arnailis Arnailis; Yunaidi Yunaidi (LPPM Institut Seni Indonesia Padangpanjang, 2025)
In Salawat Dulang performances, there are specific roles known as Induak (mother) and Anak (child). Each plays a distinct part in bringing the performance to life. This study aims to explore the roles and functions of Induak and anak in the Salawat Dulang art form as performed by the Sinar Barapi Group in Nagari Pariangan, Pariangan District, Tanah Datar Regency. The research employs qualitative methods, gathering data through interviews, literature reviews, and documentation to support the findings. In Salawat Dulang, the Induak serves multiple roles: preacher, lead singer, musician, creator, and composer. Meanwhile, the Anak acts as the Induak's counterpart, supporting as a co-preacher, backup singer, accompanying musician, co-creator, and co-composer. The dynamic between Induak and anak is inseparable; their interdependence is key to ensuring the performance flows smoothly from start to finish. This relationship is reflected in a traditional Minangkabau proverb: